Relationships between HIV/AIDS knowledge, attitude and practice and media exposure on HIV/AIDS: a cross sectional survey of adolescent Islamiyya girls in northeast Nigeria / Adamu Muhammad Hamid and Ezhar Tamam - Muhammad Hamid, Adamu; Tamam, Ezhar (Faculty of Communication & Media Studies, 2018)
Media exposure on HIV/AIDS among adolescents in the sub-Saharan Africa has been reported as low in the early 2000s but now given growth in infrastructure and development in technology and program appeal, there emerges a need for reassessment. Given that communication particularly through the media is considered as a major preventive strategy to addressing the spread of the epidemic, this study investigates the media exposure, knowledge, attitude and practice (KAP) of adolescent Islamiyya girls in Northeast Nigeria on HIV/AIDS as a predominantly Muslim society against the background of earlier studies which have shown that Muslim communities which were hitherto considered protected are now witnessing a rapid evidence of an advancing HIV/AIDS epidemic. And because of peculiar cultural and social practices women and girls are the worst affected. Media exposure on HIV/AIDS messages is considered a principal variable associated with safe attitudes and practice on the disease’s prevention which was mainly investigated among the girls as potential mothers. The main objectives of the study were to determine the girls’ patterns of media exposure and their KAP statuses in relation to HIV/AIDS through questionnaire survey. Based on Hierarchy of Effects model, hypotheses were posed to test the relationships between HIV/AIDS media exposure and HIV/AIDS knowledge, safe practice and safe attitudes among the girls, and relationship among the KAP variables. Survey will be administered on a sample of 487 Islamiyya girls in Bauchi. This study finds that while mass media exposure is not a significant predictor of HIV/AIDS safe practice and favorable attitude, it is a significant predictor of HIV/AIDS knowledge. While HIV/AIDS knowledge is a significant predictor of both HIV/AIDS favorable attitude and safe practice.